Design and Development of a Bacteria Incubator Based on Arduino Mega Microcontroller with LCD Touch Screen Display - Aditya Hermawan; Mohammad Rofi’i; Pramesti Kusumaningtyas (Jurnal Kesehatan dan Kedokteran, 2025)
The bacterial incubator plays a crucial role in culturing microorganisms, particularly in biotechnology research and its applications. This research focuses on the development of a bacterial incubator system utilizing the Arduino Mega2560 microcontroller, operating within a temperature range of 35°C to 50°C. The system incorporates a BME280 sensor for temperature and humidity detection, a TFT touchscreen LCD for user interaction, and an integrated control mechanism for regulating both temperature and incubation duration. Performance testing involved comparing sensor readings from the prototype against standard measuring devices, yielding an average temperature deviation of 0.61%, indicating reliable and precise performance. The device also features automatic regulation of environmental conditions and real-time data visualization, ensuring consistent incubation settings based on predefined criteria. Overall, testing confirmed that the incubator performs effectively and aligns with the intended design parameters.